Quality of life and the related factors in spouses of veterans with chronic spinal cord injury - Ebrahimzadeh, Mohammad Hossein (BioMed Central, 2013)
BACKGROUND: The quality of life (QOL) of caregivers of individuals with chronic spinal cord injuries may be affected by several factors. Moreover, this issue is yet to be documented fully in the literature. The purpose of this study was to evaluate the health related quality of life of spouses who act as primary caregivers of veterans with chronic spinal cord injuries in Iran. METHODS: The study consisted of 72 wives of 72 veterans who were categorized as spinal cord injured patients based on the American Spinal Injury Association (ASIA) classification. Health related quality of life was assessed by the Short Form (SF-36) Health Survey. Pearson's correlation was carried out to find any correlation between demographic variables with SF-36 dimensions. To find the effect of the factors like age, employment status, duration of care giving, education, presence or absence of knee osteoarthritis, and mechanical back pain on different domains of the SF-36 health survey, Multivariate analysis of variance (MANOVA) was used. RESULTS: The mean age of the participants was 44.7 years. According to the ASIA classification 88.9% and 11.1% of the veterans were paraplegic and tetraplegic respectively. Fifty percent of them had a complete injury (ASIA A) and 85% of the spouses were exclusive care givers. All of the SF-36 scores of the spouses were significantly lower than the normal population. Pearson's correlation demonstrated a negative significant correlation between both age and duration of caring with the PF domain. The number of children had a negative correlation with RE and VT. CONCLUSION: The burden of caregiving can impact the QOL of caregivers and cause health problems. These problems can cause limitations for caregiver spouses and it can lead to a decrease in the quality of given care.